2018
DOI: 10.1016/j.ijnss.2017.12.011
|View full text |Cite
|
Sign up to set email alerts
|

The necessity and possibility of implementation of nurse prescribing in China: An international perspective

Abstract: Background The number of countries where nurses are legally permitted to prescribe has grown rapidly due to a variety of external and internal forces. Despite its international popularity, nurse prescribing has not yet been implemented in China widely. Objective The intent of this paper is to review the current international literature regarding nurse prescribing so as to explore the necessity and possibility of implementation of nurse prescribing in China and classify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 59 publications
1
23
0
1
Order By: Relevance
“…It is worth mentioning that the variety of nurse specialists influenced their attitudes and beliefs on nurse prescribing, and we found acertain variety of nurse specialists, such as nurse specialists in diabetes, wound, emergency, geriatric and hospice specialties, had higher willingness in nurse prescribing than other specialties (see Table 4 ). This is in agreement with the results of our earlier paper (Ling et al., 2017 ), in which we found that nursing prescribing mainly targets patients with chronic diseases who are in stable condition and need long‐term medication, terminally ill patients who need palliative care, and patients in an emergency state who need first aid. Our findings reveal that the variety of nurse specialists impacts the degree of their intentions on nurse prescribing.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is worth mentioning that the variety of nurse specialists influenced their attitudes and beliefs on nurse prescribing, and we found acertain variety of nurse specialists, such as nurse specialists in diabetes, wound, emergency, geriatric and hospice specialties, had higher willingness in nurse prescribing than other specialties (see Table 4 ). This is in agreement with the results of our earlier paper (Ling et al., 2017 ), in which we found that nursing prescribing mainly targets patients with chronic diseases who are in stable condition and need long‐term medication, terminally ill patients who need palliative care, and patients in an emergency state who need first aid. Our findings reveal that the variety of nurse specialists impacts the degree of their intentions on nurse prescribing.…”
Section: Discussionsupporting
confidence: 93%
“…The scale is constructed mainly by four steps as follows. Firstly, an item pool with 38 items was constructed by literature review (Ling, et al, 2017; seven items), group discussion (16 items) and referring to a questionnaire developed by Patel et al (2009;15 items). Secondly, ten nurse specialists who were from ICU (n = 2), ER (n = 2), Orthopedics Dept.…”
Section: Items)mentioning
confidence: 99%
“…Ling et al (2018) conducted a systematic review of the available literature and determined the necessity of development and the possibility of implementing the nurse prescribing role in China. Moreover, the results of these researches indicated the positive attitudes of the nurses regarding nurse prescribing [ 23 ]. The results of LockWood et al (2008) on the attitude of specialist clinical nurses in Ireland indicated similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the nurses’ preparedness is vital to prescription, and their eligibility is among the critical factors for the successful implementation of nursing prescribing. When deciding on licensing the nurses to prescribe medications, academic qualifications and work experience should be accurately considered [ 23 ]. The most frequently mentioned barriers regarding the attitudes towards the nurse prescribing in ICU consisted of lack of legitimacy, the opposition of physicians, lack of support by nursing managers, lack of education and knowledge, fear from the legal consequences, lack of clinical experience, not considering rewards and benefits, and lack of financial support.…”
Section: Discussionmentioning
confidence: 99%
“…Internationally, independent nurse prescribing has been introduced in a variety of countries including Australia, Canada, Ireland, Spain, New Zealand, Norway, South Africa, Sweden, the Netherlands, United Kingdom, United States of America (Kroezen et al, 2011;Gielen et al, 2014), Israel and Poland. China are also considering the adoption of this role by nurses (Ling et al, 2018). The freedom to prescribe independently varies considerably between countries; "non-medical prescribing" can therefore range internationally from access to a limited formulary to a wide and flexible authority (Gielen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%